1972
DOI: 10.1159/000178270
|View full text |Cite
|
Sign up to set email alerts
|

Central α-Adrenergic Regulation of Growth Hormone and Insulin

Abstract: Serum growth hormone (GH) fell and serum insulin (IRI) rose within 30 min following infusion of phentolamine, an α-adrenergic blocking agent, into the anterior hypothalamus or third ventricle of conscious, fasted baboons. GH and IRI were unchanged following intravenous infusion systemically of phentolamine at doses 2 to 4 times greater than given centrally, indicating that the reciprocal changes in GH and IRI did not result from direct action of phentolamine on the adenohypophysis and pancreatic islets. Rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1974
1974
1987
1987

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…kg -t-min -1, may stimulate a central/%adrenergic pathway capable of mediating increased insulin secretion. Toivola et al [13] found that the a-adrenergic blocking drug, phentolamine, elevates peripheral insulin levels when placed in the hypothalamus of baboons. Furthermore, several authors have drawn attention to the modulation of insulin secretion by the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…kg -t-min -1, may stimulate a central/%adrenergic pathway capable of mediating increased insulin secretion. Toivola et al [13] found that the a-adrenergic blocking drug, phentolamine, elevates peripheral insulin levels when placed in the hypothalamus of baboons. Furthermore, several authors have drawn attention to the modulation of insulin secretion by the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond these direct effects of adrenergic secretion, adrenergic recruitment, and coordination of glucagon, cortisol and growth hormone secretion may serve as an important reinforcement to other mechanisms increasing the secretion of these hormones, thereby augmenting the overall glycemic response. Growth hormone (71)(72)(73) and cortisol by way of ACTH secretion (72,74) are both increased by adrenergic hypothalamic mechanisms. Glucagon secretion can also be increased by adrenergic activity (75)(76)(77)(78).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been demonstrated that perfusion of the hypothalamus in baboons with the alfa-adrenergic blocking agent, phentolamine, induced an enhancement of basal insulin secretion when administered in a concentration which had no effect when given to the systematic circulation [7]. Furthermore, lesions applied to the ventromedial nuclei of the hypothalamus were accompanied by hyperinsulinemia [8].…”
Section: Discussionmentioning
confidence: 99%